2005
DOI: 10.1057/palgrave.ejis.3000541
|View full text |Cite
|
Sign up to set email alerts
|

The turnaround of the London Ambulance Service Computer-Aided Despatch system (LASCAD)

Abstract: The implementation of the Computer-Aided Despatch system at the London Ambulance Service has been one of the most notorious cases of failure within the information systems (IS) literature. What is less well known is that there followed, some time later, a much more successful implementation, described as a turnaround. This paper, based on a case study approach, describes the context and detail of that implementation. A framework from the literature, used in an analysis of the initial failure, is used to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 24 publications
5
61
2
2
Order By: Relevance
“…System quality was not found to be related to system use. This finding is unexpected and inconsistent with previous studies where system quality is reported to have a significantly positive influence on system use (DeLone & McLean 2003;Fitzgerald & Russo 2005). The different types of applications investigated and the different contexts can explain differences amongst the findings of this study and the research in previous studies.…”
Section: Structural Modelcontrasting
confidence: 57%
See 1 more Smart Citation
“…System quality was not found to be related to system use. This finding is unexpected and inconsistent with previous studies where system quality is reported to have a significantly positive influence on system use (DeLone & McLean 2003;Fitzgerald & Russo 2005). The different types of applications investigated and the different contexts can explain differences amongst the findings of this study and the research in previous studies.…”
Section: Structural Modelcontrasting
confidence: 57%
“…This finding suggests that the quality of service does not influence the use of the system. This is inconsistent with previous studies where service quality is reported to have a significant influence on system use (Caldeira & Ward 2002;Fitzgerald & Russo 2005).…”
Section: Structural Modelcontrasting
confidence: 56%
“…Nonetheless, many case studies of IS failure are described and discussed in the literature, and different causes and consequences of IS failure have been proposed (e.g. Avison and Wilson 2002, Barker and Frolick 2003, Beynon-Davies 19951997;Bussen and Myers 1997;Fitzgerald and Russo 2005;McGrath 2002;Nelson 2007;Pan et al 2008;.…”
Section: Information Systems Successmentioning
confidence: 99%
“…Requirements engineering is concerned with the production of specifications, including those for implementation, deployment and maintenance of the system [170]. If the system is not implemented correctly then it can have disastrous effects, as shown in [61] which described the impact of the most notorious information system failure in recent times (the London Ambulance Fiasco). To create reliable systems, a formal methodology or language should be used for the creation of the system requirements.…”
Section: Specification and Verificationmentioning
confidence: 99%